A Literature Review on Sustaining Engagement: Cloud Data Management in Education during Crisis - Ma. Abegail Tulas (Southeast Asian Journal of Science and Technology, 2025)
This literature review systematically examines the critical role of Cloud Data Management (CDM) insustaining educational engagement during crisis, with direct implications for today’s evolving hybrid and digitally learningenvironments. From the urgent global shift to remote learning, the study consolidates research from 2020-2025 to analyzehow technologies transition from supportive tools to essential pillars of educational continuity and resilience. This reviewidentifies and categorizes the key features of CDM such as scalable infrastructure, integrated collaborative teachingplatforms, and robust security protocols that enable dynamic teaching and active learning when traditional classrooms areinaccessible. Additionally, it synthesizes the predominant financial, technical, and governance barriers that hinder effectiveimplementation, including unpredictable costs, legacy system integration, data silos, and vulnerabilities in security models.Furthermore, the study critically appraises the methodologies and metrics used to measure student engagement in cloudbased environments, noting a reliance on simplistic behavioral data. The findings underscore that education marked bypersistent digital transformation and preparedness for future disruptions; mastering CDM is not merely technological butstrategic. It requires principled governnce, ethical data application, and equitable access to build resilient, engaging, andhuman-centered learning environment. This review provides educators, administrators, and policymakers with an evidencebased framework to navigate the complexities of cloud adoption, ensuring that educational engagement endures throughuncertainty